Iodosylbenzene and iodylbenzene adducts of cerium(iv) complexes bearing chelating oxygen ligands. Issue 13 (9th March 2016) - Au-Yeung, Ka-Chun; So, Yat-Ming; Wang, Guo-Cang; Sung, Herman H.-Y.; Williams, Ian D.; Leung, Wa-Hung
Abstract : Reactions of [Ce IV (LOEt )2 Cl2 ] (LOEt − = [Co(η 5 -C5 H5 ){P(O)(OEt)2 }3 ] − ) with PhIO and PhIO2 afford [Ce IV (LOEt )2 {OI(Cl)Ph}2 ] and [Ce IV (LOEt )2 {OI(O)ClPh}2 ], respectively, which have been characterised by X-ray crystallography. Abstract : Reactions of [Ce IV (LOEt )2 Cl2 ] (LOEt − = [Co(η 5 -C5 H5 ){P(O)(OEt)2 }3 ] − ) and [CeIV2(μ-O){N(Pr i 2 PO)2 }4 Cl2 ] with PhIO afford the λ3 -iodane complexes [Ce IV (LOEt )2 {OI(Cl)Ph}2 ] and [CeIV2{N(Pr i 2 PO)2 }3 {OI(Cl)Ph}], respectively, whereas that between [Ce IV (LOEt )2 Cl2 ] and PhIO2 or excess PhIO yields the λ5 -iodane adduct [Ce IV (LOEt )2 {OI(O)ClPh}2 ]. The crystal structures of the Ce IV λ3 - and λ5 -iodane complexes have been determined and their oxo transfer reactivities have been investigated.